Principles of Interaction between the State Border Guard Service of Ukraine and Other Law Enforcement Agencies - I. I. Baidyuk (Bulletin of Kharkiv National University of Internal Affairs, 2019)
The author has studied the essence of the principles of interaction of the State Border Service with other law enforcement agencies, which is conditioned by the importance of ensuring proper protection of the state border in the current conditions of the state development. The main method of the research was the method of critical analysis, which made it possible to analyze the provisions of the current national legislation and the approaches in the scientific doctrine to understanding the principles of interaction of the State Border Service of Ukraine with other law enforcement agencies. The content of the concept of “principles of interaction” has been clarified. The definition of the concept of “principles of interaction of the State Border Guard Service with other law enforcement agencies” has been formulated. The author has revealed the content of such principles of interaction of the Border Guard Service with other law enforcement agencies as: the rule of law, legality, respect and observance of human and citizen rights and freedoms, equality of the subjects of interaction, scientific nature, planning, personal responsibility of the management and employees of the subjects of interaction for its results, combination of open, secret and conspiratorial forms and methods of activity, promptness and professionalism of the employees of the subjects of interaction, coherence of actions of the subjects of interaction and independence of each of them within their powers. The author has offered to classify the principles of interaction of the Border Guard Service with other law enforcement agencies, by dividing them into general and special ones.